PENERAPAN APLIKASI BERBASIS ANDROID UNTUK LATIHAN TENSES - Widayati, Qoriani; Effendy, Irman ; Sopiah, Nyimas (JURNAL ILMIAH MATRIK, 2015)
Abstract: English is no longer a rare thing. All education level has this subject as their main or additional lesson at school. One of the topics learnt is grammar. Well-managed grammar skill, of course, supports the learner either in oral or written communication. In addition, this helps the learner in writing formal and non-formal text such as letter, short message, and scientific article. Tense,in which people learn how to form sentences based on some patterns, is one of the most dominant sub-topics discussed in grammar. To easing the learners understand it, the writer try to create an android based application as a learning media for learners which can be used everywhere. However, this application can only be used by android operating system smartphones. At the end, this study aimed to see the implementation of android-based English tenses application. Keywords: Practice, Tenses, Android